2012
DOI: 10.1136/thoraxjnl-2011-200018
|View full text |Cite
|
Sign up to set email alerts
|

Factors contributing to the high prevalence of multidrug-resistant tuberculosis: a study from China

Abstract: BackgroundThe rapid spread of multidrug-resistant tuberculosis (MDR-TB) has attracted global concerns. This study aimed to identify factors contributing to the high prevalence of MDR-TB in China's Heilongjiang province. Methods A cross-sectional survey following the WHO/ International Union Against Tuberculosis and Lung Disease guidelines was conducted with consecutive recruitment of patients with TB in 30 counties selected at random in Heilongjiang in 2004. A total of 1995 patients were tested for MDR-TB. Fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
71
2
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(90 citation statements)
references
References 17 publications
15
71
2
2
Order By: Relevance
“…In Ethiopia, Abate G 16 Showed MDR prevalence were more in retreatment cases (12%) than new (1.2%). In A study shown by Liang et al 17 in China , inappropriate treatment, longer delays to effective therapy were the most influential factors behind emergence of drug resistance. Retreatment patients were 5.48 times and those with previous INH and RMP therapy for more than 180 days were 4.82 times more likely to develop MDR-TB.…”
Section: Discussionmentioning
confidence: 99%
“…In Ethiopia, Abate G 16 Showed MDR prevalence were more in retreatment cases (12%) than new (1.2%). In A study shown by Liang et al 17 in China , inappropriate treatment, longer delays to effective therapy were the most influential factors behind emergence of drug resistance. Retreatment patients were 5.48 times and those with previous INH and RMP therapy for more than 180 days were 4.82 times more likely to develop MDR-TB.…”
Section: Discussionmentioning
confidence: 99%
“…Those who had a failure or default treatment were more likely to get massive hemoptysis. Liang L et al reported that the top three reasons for failure to complete the TB treatment regimens in China were poor knowledge, financial burden and treatment side effects [7]. Poor knowledge about TB and mild symptoms,many patients tended to delay initiating treatment, prolong the time that patients carry the TB bacteria and allow the disease to progress without proper intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Multidrug Resistant Tuberculosis (MDR-TB), is caused by mycobactria isolates which are resistant to, at least, Isoniazid (INH) and, Rifampin (RIF) (5,6). Delayed diagnosis and inappropriate treatment of tuberculosis may result in constantly increasing severity, mortality, spreading and the emergence of MDR-TB (7)(8)(9). Annually, MDR-TB is estimated to afflict 490,000 cases, or 5% of the global TB burden.…”
Section: Introductionmentioning
confidence: 99%